2014
DOI: 10.3177/jnsv.60.152
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Salivary Calcium Concentration and Differences in Bone Mineral Density Level in Female Rats

Abstract: Summary It has not yet been examined whether salivary calcium levels reflect changes in bone mass. The purpose of this study was to investigate the relationship between salivary calcium concentration and differences in bone mineral density due to estrogen deficiency and/or different calcium intake levels in female rats. In Experiment 1, the animals (n514) were divided into an ovariectomized group (OVX) (n58, 0.6% calcium diet) and a shamoperated group (Sham) (n56, 0.6% calcium diet). The bone mineral density (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The results of this study observed BMD of tibial diaphysis in OC group was higher than that in Sham group despite the opposite result in BMD of tibial proximal metaphysis. Similar trends have been observed in our previous studies that also used OVX rats 13 . These findings indicate that tibial diaphysis may be more sensitive than proximal metaphysis.…”
Section: Bmc Of Tibial Diaphysis (G)supporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study observed BMD of tibial diaphysis in OC group was higher than that in Sham group despite the opposite result in BMD of tibial proximal metaphysis. Similar trends have been observed in our previous studies that also used OVX rats 13 . These findings indicate that tibial diaphysis may be more sensitive than proximal metaphysis.…”
Section: Bmc Of Tibial Diaphysis (G)supporting
confidence: 91%
“…The bone strength of the femoral midshafts were evaluated by a three-point bending test (DYN-1255; IIO DENKI, Tokyo, Japan) using previously described methods (distance between the fulcrum 1 cm, plunger speed 100 mm/minute, full scale 50 kg, chart speed 120 cm/min) [ 13 ]. ‘‘Breaking force’’ refers to the loading weight (gravitational acceleration) required for bone breaking.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies report that estrogen is the most important hormone in maintaining bone mass and that a deficiency of this hormone is a major cause of bone loss associated with age in both genders (37)(38)(39). Notably, when the circulating estrogen level decreases, calcium in the bones rapidly decreases, and calcium loss occurs via an increase in its urinary excretion (40). In the current study, rat blood estradiol level was gauged using an ELISA kit.…”
Section: Discussionmentioning
confidence: 99%
“…The tibia was divided into five areas, and the region of interest (ROI) was set as the proximal two areas using a modified division method [19]. The same technician, who was blinded to the treatment assignments, conducted the DXA analyses.…”
Section: Methodsmentioning
confidence: 99%